Experimental study of the influence of starting pumping units on the value of oil pressure in oil-trunk pipelines - S.Ia. Grygorskyi, M.D. Serediuk (JOURNAL OF HYDROCARBON POWER ENGINEERING, 2018)
Having made experimental studies by modern measuring instruments at the existing pipeline we obtained pressure change regularities during unsteady hydrodynamic processes taking into account operation technology and characteristics of domestic oil pipeline pumping equipment. There have been studied regularities of the rotor speed and pressure of NM oil pumps variations over time at their starting. There is revealed the change in transported oil pressure over time at the inlet and outlet of a pumping station during pumping units startings. There have been built exponential dependences of the value of abrupt reduction and increase of oil pressure on the distance to the place of disturbance occurrence. The intensity of a low and high oil pressure wave damping in the pipeline are estimated.